BULGARIAN EMPLOYMENT POLICY: PRIORITIES AND DIRECTIONS 2017 - Arabska, Ekaterina (Journal of process management and new technologies, 2017)
Development of labor market and employment policy in Bulgaria in contemporary dynamic conditions of social and economic life is in close relation to the European policies and programs and the needs of creating conditions for raising the level of employability of some special target groups on the labor market determined as the most vulnerable and needing particular measures of support. Current study makes analyses of priorities and directions in Bulgarian national employment policy for 2017 as set into the National action plan on employment considering a number of strategic and legislative documents on both national and European level. The general conclusions are focused on the systematization of actions and the importance of social dialogue.